Dampak Islamisasi Kerajaan Padjajaran: Sistim Pendidikan dan Nilai-Nilai Sosial dalam Kehidupan Masyarakat Sunda - Supendi, Usman; Pribadi, Syofiah; Murni, Fitria Eka Dewi (Attractive : Innovative Education Journal, 2024)
This research aims to investigate the impact of Islamization in the Kingdom of Padjajaran, particularly in the transformation of the education system and changes in the social values of Sundanese society. Using a qualitative approach and historical case study, the focus of the research involves the region of West Java that was in the past part of the Kingdom of Padjajaran. The results show that Islamization affected religious changes and included significant transformations in the education system, with Islamic boarding schools and madrasahs becoming centres of knowledge offering holistic education. In addition, the social values of Sundanese society also changed, encompassing the concepts of justice, tolerance and brotherhood introduced by Islamic teachings. Although the Kingdom of Padjajaran did not become a fully independent Islamic kingdom, the influence of Islam continued to infiltrate and shape its cultural and social aspects, making a significant contribution towards understanding the role of Islam in shaping the identity and social life of Sundanese society during this period. Keywords: Padjajaran Kingdom, Education System, Sundanese Society